Superficial Ulcerating Rheumatoid Necrobiosis Associated with Methotrexate Use in a Patient with Rheumatoid Arthritis - Austin Cusick; Amandeep Goyal; Ashley H. Merten; Andrew Virata; Rahul Sehgal; Pankaj Bansal (European Medical Journal, 2020)
Methotrexate, a disease-modifying antirheumatic drug, is fundamental to limiting progression in several rheumatic diseases such as rheumatoid arthritis (RA). However, methotrexate is also associated with various significant adverse effects. Of note, there are several dermatologic manifestations attributed to methotrexate therapy. In particular, accelerated nodulosis and panniculitis are linked to methotrexate therapy in the current literature. The authors present the case of a 55-year-old Caucasian female with seropositive erosive RA who developed superficial ulcerating rheumatoid necrobiosis (SURN), secondary to methotrexate therapy. The patient’s treatment consisted of methotrexate discontinuation, topical clobetasol, and initiation of leflunomide as a replacement of methotrexate. Follow-up evaluation confirmed resolution of SURN over time and maintained low disease RA activity with leflunomide.